2007
DOI: 10.1302/0301-620x.89b7.18452
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of the angle of immobilisation of the knee to the force applied to the extensor mechanism when partially weight-bearing

Abstract: We describe the influence of the angle of immobilisation during partial weight-bearing on the forces across the extensor mechanism of the knee. Gait analysis was performed on eight healthy male subjects with the right knee in an orthotic brace locked at 0 degree, 10 degrees, 20 degrees and 30 degrees, with the brace unlocked and also without a brace. The ground reaction force, the angle of the knee and the net external flexion movement about the knee were measured and the extensor mechanism force was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Raw data were filtered using a fourth order low-pass Butterworth filter with a cut-off frequency of 6 Hz for kinematic data and 15 Hz for kinetic data [13]. The lower extremity was modeled as a rigid, linked-segment system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw data were filtered using a fourth order low-pass Butterworth filter with a cut-off frequency of 6 Hz for kinematic data and 15 Hz for kinetic data [13]. The lower extremity was modeled as a rigid, linked-segment system.…”
Section: Discussionmentioning
confidence: 99%
“…Knee torque was calculated from the model developed in Visual 3D software. Assuming that in a semistatic situation the two torques of the extensor mechanism and knee are equal (τ em = τ knee ) [2,13], the unknown τ em in Eq. (1) can be replaced by knee torque.…”
Section: Discussionmentioning
confidence: 99%
“…The kinematics of the joints were recorded at a frequency of 100 Hz, employing 36 retro-reflective markers placed strategically on specific anatomical landmarks such as the anterior superior iliac spine (ASIS) and posterior superior iliac spine (PSIS), femoral condyles and malleoli, heels, and the base of the first, second, and fifth metatarsals. These markers facilitated the determination of joint centers and segments of the lower extremities 27 , 28 . Additionally, four rigid-shell clusters were affixed to the athletes' thighs and legs to monitor the motion of these segments.…”
Section: Methodsmentioning
confidence: 99%
“…One of the primary ways of limiting joint motion during this period is through knee bracing [1,2,7,8]. Previous research has indicated that braces are effective in restricting static knee range of motion, although the metabolic and physiologic cost of walking increases when using a brace [9][10][11][12][13]. However, little is known about how use of a brace alters functional activities such as unilateral balance and gait [14,15].…”
Section: Introductionmentioning
confidence: 99%